Análise óptica de folhas e flores de plantas - Janeczko, César (2019)
The objective of this work was to perform measurement experiments using optical microscopy techniques to extract some physical and chemical characteristics of leaves and flowers by an indirect way, in order to understand the relation of the physical / chemical structure of leaves and flowers with relation to its functionalities and the iteration with external agents. As well as spectrophotometric measurements in order to analyze if there is correlation of pigments in leaves and flowers, since the “flower is considered a modified leaf”. Through microscopic image processing, a colored mapping of the leaf and flower surface was developed by indirect measurement of the contact angle at the interface between the water drop, the surface and the air. Thus providing, from a two-dimensional image three-dimensional data, interrelated to the physical-chemical nature of the analyzed surface, through the wettability of the surface. The volume of the drop was calculated by the reflected brightness on the surface below the drop, when illuminated by the proposed illumination; the diameter of the droplet measured by circle detection algorithm and the contact angle was calculated by the top-down method proposed (DUTRA et al., 2017), subsequently showing a colored surface mapping. Several analyzes have been done to validate the method and demonstrate that the wettability information has correspondence with biological functions. In orchidaceae Cattleya warneri, young leaves are hydrophobic, while old leaves become hydrophilic, because of continual exposure to changes in the environment over time. The flowers are hydrophobic due to their function of visual and tactile attractiveness for pollination of animals, as well as the self-cleaning of dirt and pathogens. By analyzing 22 leaf surfaces, we corroborate that the adaxial surfaces of the leaves are hydrophilic and the abaxial surfaces are hydrophobic, and this may be related to a greater stomatal density in the abaxial than in the adaxial side. Other factors, such as the high density of trichomes are also usually related to the lower wettability of the leaves. Surface mapping has proven to be a powerful tool for regular plant monitoring. Moreover, it is a scientific tool able to provide analyzes on surfaces of any type at the interfaces with the drop in nanoscale level. Here, we can map the entire surface, not just in the edges as in the side view methods. In Appendix A, we find a vast bibliographical review about pigments, their extraction and peculiarities, and the spectrometric and chromatographic forms of analysis. The results showed a correlation between the substances extracted from flowers and leaves. Such correlation is not indicated in the literature, although it is postulated that flower is a modified leaf.